2019
DOI: 10.1111/jwip.12127
|View full text |Cite
|
Sign up to set email alerts
|

Food origin labels in Ghana: Finding inspiration in the European geographical indications system on honey

Abstract: Geographical indication (GI) identifies goods originating from a particular territory, where certain qualities and reputation of the product are essentially attributed to that origin. GIs connote value addition hence a tool for livelihood improvement among producers of local products. This is especially the case for honey, which is mainly produced rural areas in Ghana, where there are few other income sources.However, GIs are unknown in the country. This paper discusses various elements and storylines that com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 19 publications
1
10
0
1
Order By: Relevance
“…With the introduction of GI, beekeeping seems to live up to this expectation as the number of producers and beekeeping cooperative memberships increased, producer prices of white and brown honey increased, and white honey sales grew, as have the numbers of market outlets locally and in large urban areas. As such, seemingly the GI formation for Oku white honey mirrored the anticipated benefits theorized by Jena and Grote (2010) and argued for in other theoretical and empirical studies (Benni and Reviron, 2009;Cei et al, 2018), including studies of potential GI honeys (Egelyng et al, 2017;Mwakaje et al, 2018;Besah-Adanu et al, 2019). Positive impacts on local communities (Vandecandelaere et al, 2009), even if not engaged in honey production, have also been observed as one of the spillovers of GI, such as an expansion in tourist activities.…”
Section: Livelihood Benefits Based On Short-term Price and Production Expansionsupporting
confidence: 55%
See 2 more Smart Citations
“…With the introduction of GI, beekeeping seems to live up to this expectation as the number of producers and beekeeping cooperative memberships increased, producer prices of white and brown honey increased, and white honey sales grew, as have the numbers of market outlets locally and in large urban areas. As such, seemingly the GI formation for Oku white honey mirrored the anticipated benefits theorized by Jena and Grote (2010) and argued for in other theoretical and empirical studies (Benni and Reviron, 2009;Cei et al, 2018), including studies of potential GI honeys (Egelyng et al, 2017;Mwakaje et al, 2018;Besah-Adanu et al, 2019). Positive impacts on local communities (Vandecandelaere et al, 2009), even if not engaged in honey production, have also been observed as one of the spillovers of GI, such as an expansion in tourist activities.…”
Section: Livelihood Benefits Based On Short-term Price and Production Expansionsupporting
confidence: 55%
“…Giovannucci et al (2009) emphasize that despite the originality of a potential GI product, benefits will not accrue to stakeholders without the support of the legal and institutional frameworks. Other factors that support GI registration of products include collective action, prices and market for the product, specificity and reputation of the product, support from actors along the value chain, production methods and a link between product characteristics to history or tradition of the geographical area (Bramley et al, 2013;Egelyng et al, 2017), also for honey (Besah-Adanu et al, 2019). The effects of hybrid institutions also depend on product types and value chain characteristics (Lambin et al, 2014).…”
Section: Conceptual Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…Ghana is among the few African countries certified to export honey to the EU market; however, the export so far is not remarkable. Beekeepers of Ghana, therefore, would like to follow the example of the Oku White honey, which has received the African PGI label, resulting in increasing sales and prices, together with exports to the EU [47]. In Chile, neither the national GI labels nor the public certification trademark is widely used among the producers; therefore they cannot meet their original expectations to increase market share and to reach export markets [48].…”
Section: The Market Size Of Gi Productsmentioning
confidence: 99%
“…This is a particularly relevant barrier in cases of potential GIs open to international markets, where the risks of elite capture of the GI benefits may exclude the poorest producers in rural areas, as other experiences from Latina America have demonstrated [59]. Therefore, in order to make the initiative more resilient, then avoiding possible failures emerged in other similar cases [60], supportive elements are of paramount importance, in the form of GI legislation, state institutions, and local and international NGOs [61]. Moreover, the government of Ghana should review the laws governing the registration and operation of Geographical Indications in Ghana.…”
Section: Discussionmentioning
confidence: 99%